Astrocytic junctional adhesion molecule-A regulates T-cell entry past the glia limitans to promote central nervous system autoimmune attack. Issue 2 (18th February 2022) - Amatruda, Mario; Chapouly, Candice; Woo, Viola; Safavi, Farinaz; Zhang, Joy; Dai, David; Therattil, Anthony; Moon, Chang; Villavicencio, Jorge; Gordon, Alexandra; Parkos, Charles; Horng, Sam
Abstract: Contact-mediated interactions between the astrocytic endfeet and infiltrating immune cells within the perivascular space are underexplored, yet represent potential regulatory check-points against CNS autoimmune disease and disability. Reactive astrocytes upregulate junctional adhesion molecule-A, an immunoglobulin-like cell surface receptor that binds to T cells via its ligand, the integrin, lymphocyte function-associated antigen-1. Here, we tested the role of astrocytic junctional adhesion molecule-A in regulating CNS autoinflammatory disease. In cell co-cultures, we found that junctional adhesion molecule-A-mediated signalling between astrocytes and T cells increases levels of matrix metalloproteinase-2, C–C motif chemokine ligand 2 and granulocyte-macrophage colony-stimulating factor, pro-inflammatory factors driving lymphocyte entry and pathogenicity in multiple sclerosis and experimental autoimmune encephalomyelitis, an animal model of CNS autoimmune disease. In experimental autoimmune encephalomyelitis, mice with astrocyte-specific JAM-A deletion ( mGFAP:CreJAM-A fl/fl ) exhibit decreased levels of matrix metalloproteinase-2, reduced ability of T cells to infiltrate the CNS parenchyma from the perivascular spaces and a milder histopathological and clinical course of disease compared with wild-type controls ( JAM-A fl/fl ). Treatment of wild-type mice with intraperitoneal injection of soluble junctional adhesion molecule-A blocking peptide decreases the severity of experimental autoimmune encephalomyelitis, highlighting the potential of contact-mediated astrocyte–immune cell signalling as a novel translational target against neuroinflammatory disease. Abstract : Amatruda et al . report that the astrocytic immune cell receptor, junctional adhesion molecule-A, increases levels of matrix metalloproteinase-2 and promotes T-cell entry into the CNS during autoimmune attack. Blocking contact-mediated astrocyte immune cell signals represents a novel therapeutic approach against multiple sclerosis and other CNS autoinflammatory diseases. Graphical Abstract: Graphical Abstract